The effect of low temperature heat treatment on stress corrosion crack initiation in machined 316L stainless steel in high-temperature hydrogenated water. (1st April 2021) - Chang, Litao; Mukahiwa, Kudzanai; Duff, Jonathan; Burke, M. Grace; Scenini, Fabio
Abstract: A notable reduction of the stress corrosion cracking (SCC) initiation susceptibility was identified for machined cold-rolled 316L stainless steel that received a 650°C/10 hours heat-treatment prior to slow strain rate tensile (SSRT) testing in high-temperature hydrogenated water. The cracks per unit area of the machined surface of heat-treated specimens decreased by 50% compared to as-machined surfaces, and by >70% with respect to polished surfaces. The results were ascribed to recrystallization of the ultrafine-grains present in the outer deformation layer of the machined surface, which resulted in a reduction of the tensile residual stress and nano-indentation hardness. Graphical abstract: Image, graphical abstract